STUDI TENTANG FAKTOR â FAKTOR YANG MEMPENGARUHI PERTUMBUHAN DAN PERKEMBANGAN PADA BALITA DI DESA PENGALANGAN RW 03 MENGANTI GRESIK - ., Dianita Primihastuti, (D3 Kebidanan, 2013)
Growth and development is the main thing, it is essential and distinctive in children that are different but inter-related and difficult to separate. Several factors influence the process of growth and developments; internal factors and external factors that include nurturing environmental factors, stimulating factors and nutritional factors. Among these various factors, one more factor affecting the growth and development process is nurturing environment factors. If the parenting environment is better than the growth and development of infants would be better, whereas, if the parenting environment is not good, then the toddlers growth and development would become less good. Based on the results of observations made by the author in Pengalangan village, RW 03 Menganti Gresik, It was found that many toddlers who werelate in growth and development. The research design of this study was "Descriptive". The purpose of writing a scientific paper is to identify the nurturing environmental factors, stimulating factors and nutritional factors affecting growth and development in infants. The population were 28 people, the samples taken was mothers who had their babyâs growth and developmental delays by 28 people. The sampling method used was "Total sampling". Data were collected by questionnaire and examination SDIDTK. Based on the results, the factors influence the growth and development of the caregiving environment as much as 25 respondents (89.3%), stimulation by 23 respondents (82.1%), and nutrition by 22 respondents (78.6%). In this case, those factors affect the process of growth and development, so if parents are less optimal to look after may cause delays in growth and development to infants.Keywords : growth and development, nurturing environment factor, stimulation factor and nutritional factor.